Tissue microarray analysis reveals site-specific prevalence of oncogene amplifications in head and neck squamous cell carcinoma - Freier, Kolja; Joos, Stefan; Flechtenmacher, Christa; Devens, Frauke; Benner, Axel; Bosch, Franz X.; Lichter, Peter; Hofele, Christof (Cancer research, 2003)
Fluorescence in situ hybridization was applied on a collection of 609 squamous cell carcinomas of the head and neck (HNSCCs),including 511 primary carcinomas of different clinical stage and anatomical localization and 98 recurrent carcinomas, second primary carcinomas, and regional metastases on a tissue microarray. The overall prevalence of amplifications of five oncogenes analyzed was 34.5% for CCND1, 12.7% for EGFR, 8.8% for MYC, 6.2% for ZNF217, and 3.6% for ERBB2. CCND1 amplifications were associated with the pharyngeal site in primary carcinomas (P < 0.001), whereas amplifications of ZNF217 were less frequent in pharyngeal carcinomas as compared with primary oral and laryngeal carcinomas (P = 0.02). The amplification pattern of these oncogenes suggests that different molecular pathways are involved in HNSCCs of different localizations.
Gesehen am 09.02.2021